Investigation on the lifespan of gaharu tea / Muhammad Syafiq Ridhuan Ahmad Suhaimi - Ahmad Suhaimi, Muhammad Syafiq Ridhuan (2019)
Gaharu tea is a tea that made up from leaves of Aquilaria species. This species has a lot of benefits towards human health such as anti-allergic, anti-diabetic, anti-cancer and anti-inflammatory (Yumi Zuhanis Has-Yun Hashim, 2016). In this study, Aquilaria malaccensis has been chosen as the sample due to high distribution of this species in Malaysia. Aquilaria malaccensis is one of the natural species that grow in peninsular Malaysia. This study will investigate the effect of different moisture content and the effect of different storage conditions on the lifespan of gaharu tea. The leaves will be processed using green tea processing method. it will undergo drying process at fix temperature (50°C) and pressure (0.6 bar) with different drying time which is 60 mins, 90 mins, 120 mins, 150 mins and 180 mins by using Vacuum Far-Infrared Radiation (VFIR) dryer. Another sample will undergo drying process at fix temperature (50°C, pressure (0.6 bar) and drying time (120 mins) but different storage conditions. All of the samples will be going through moisture content analysis and chemical analysis (antioxidant and bacterial colony count).